DEVELOPMENT OF STUDENT WORKSHEETS TOPIC BASED ON ENVIRONMENTAL POLLUTION MATERIALS USING THE ARGUMENT-DRIVEN INQURY (ADI) MODEL FOR SEVENTH GRADE OF JUNIOR HIGH SCHOOL STUDENTS - Febrita, Yunikmah; Sari, Monica Prima (Department of Science Education, 2025)
This research was conducted to determine the validity and practicality of the worksheets teaching materials. Based on the analysis of the activities in science learning, it was found that students were still less active in the learning process and lacked confidence in giving opinions during the ongoing learning process. One attempt which can be done to address this problem is by developing students' worksheet which can encourage students to be more active in learning. One approach we can use to develop students worksheet is using the Argument-Driven Inquiry Model, which emphasize on students' confidence in presenting their own argument in class. This development research employed three stages of the 4-D model, which consists of four stages namely define, design, develop and disseminate, Disseminate stage could not be done due to several considerations related to time constraint and expenses. The research instrument used were a validity and practicality questionnaire. This students worksheet was validated by 3 validators and tested for practicality on 5 grade VII students. The results showed that the developed students worksheet compiled and developed was very valid with a score of 80.02% and practicality by teachers of 90.29 and 90.88 at the category of very high. Therefore, this student worksheet can be implemented in learning. However, we would like to recommend for further research with regard to the Argument-Driven Inquiry so that the research is more valid.